2010
DOI: 10.3892/or_00000947
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal role for Pim-1 kinase in esophageal squamous cell carcinoma involving cell apoptosis induced by reducing Akt phosphorylation

Abstract: Abstract. It is well documented that Provirus integration site for Moloney murine leukemia virus 1 (Pim-1), as a protooncogene encoding a serine/threonine kinase with multiple cellular functions, is tightly associated with the occurrence and development of tumors. Overexpression of Pim-1 plays a critical role in the progression of several different tumors. In this study, esophageal squamous cell carcinoma (ESCC) EC9706 cells with Pim-1 siRNA treatment resulted in a clear decrease of Pim-1 levels, followed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Western blotting was performed according to standard methods as described previously (18,19). Briefly, ESCC tissues and normal esophageal tissues were lysed in a sample buffer (50 mM Tris-HCl, pH 8.0; 150 mM NaCl, 1% Triton X-100; 100 μg/ml PMSF) on ice for 30 min.…”
Section: In Situ Hybridization (Ish)mentioning
confidence: 99%
“…Western blotting was performed according to standard methods as described previously (18,19). Briefly, ESCC tissues and normal esophageal tissues were lysed in a sample buffer (50 mM Tris-HCl, pH 8.0; 150 mM NaCl, 1% Triton X-100; 100 μg/ml PMSF) on ice for 30 min.…”
Section: In Situ Hybridization (Ish)mentioning
confidence: 99%
“…Previous studies have suggested that PIM-1 is important for carcinogenesis and metastasis in numerous types of human cancer (6)(7)(8)(9)(10)(11)(12). The present study selected 4 pairs of ACC tissue and corresponding normal tissues and revealed that PIM-1 was overexpressed in ACC.…”
Section: Discussionmentioning
confidence: 94%
“…PIM-1, Pim-1 proto-oncogene, serine/threonine kinase (PIM-1) is upregulated in a number of cancer subtypes and the overexpression of PIM-1 is thought to be involved in cancer-specific apoptosis signaling pathways (6)(7)(8)(9)(10)(11)(12). Apoptosis is modulated by complex pathways that involve a series of apoptosis-associated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…High expression of the proto-oncogene PIM-1 was detected in ESCC with lymph node metastasis[ 44 ], and PIM-1 siRNA inhibited the proliferation of ESCC cells and induced apoptosis[ 45 ]. Upregulation of PIM-1 was also found in gastric glands correlated with the lymph node metastasis of gastric cancer[ 46 ].…”
Section: Resultsmentioning
confidence: 99%